A review of wire arc additive manufacturing: development, principles, process physics, implementation and current status. (31st August 2021) - Norrish, John; Polden, Joseph; Richardson, Ian
Abstract: Additive manufacturing (AM) is now recognised as a viable alternative to processes such as casting, forging, and subtractive technologies such as machining. Wire arc additive manufacturing (WAAM) has emerged as a cost-effective AM approach for component fabrication and a considerable body of literature on the subject has become available over the last 30 years. This review references the published work in a critical manner. It traces the development of WAAM, the principles of operation, materials considerations, process options, process physics, numerical simulation, process control, the current status and future research needs.